Pengaruh Manajemen Resiko Kredit Dan Resiko Pasar Terhadap Kinerja Keuangan Pada Perusahaan Perbankan - Adawiah, Roudatul; Heffi Christya Rahayu; Makmur (CV. Strata Persada Academia, 2025)
This study aims to analyze the influence of credit risk management and market risk on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A quantitative research method was applied using a purposive sampling technique, resulting in a sample of 19 banking companies. Secondary data were collected from official financial statements and analyzed using multiple linear regression, supported by F-tests, t-tests, and the coefficient of determination (R²). The findings reveal that credit risk has a negative and significant effect on financial performance, as indicated by a regression coefficient of -0.015 and a significance level below 0.05. Conversely, market risk shows a positive and significant effect, with a regression coefficient of 0.025 and a significance level below 0.05. These results suggest that higher credit risk reduces financial performance, while strategic responses to market fluctuations can enhance bank profitability. The study offers valuable insights for financial managers and regulators to improve risk management practices and ensure banking sector stability amid global economic uncertainties.